DETERMINANTS OF KNOWLEDGE SHARING BEHAVIOUR AMONG STUDENTS OF PRIVATE HIGHER EDUCATION INSTITUTIONS IN KLANG VALLEY, MALAYSIA - Eu, Chai Ni; Sumitha, Ganesharatnam (INTI International University, 2022)
Activities relating to knowledge sharing in education institutions is getting popular these days. University and college can practice knowledge sharing through initiatives like giving rewards to motivate students to share knowledge. Students who develop the knowledge sharing habit tend to carry the habit to their future workplace. Organisations need employees who are willing to share knowledge to gain competitive advantage and reduce training costs.